Education Is for the People, Not the State: Moving Beyond the Public/Private Distinction - Säfström, Carl (Philosophical Inquiry in Education, 2026)
This text aims at shifting interest from public education to the publicness of education, and it does so by discussing the very foundations of education itself. In particular this article explores the difference between the Sophists’ practice-oriented understanding of education and its autotelic aims, on the one hand, and Plato’s understanding that education is a tool to perfect the state, on the other hand. I argue that the Sophist’s understanding of education is more productive for expanding the public meaning of education beyond the conventional understandings of the public as being tied to the state. This requires a shift from seeing the state as the only legitimate owner of the goals and aims of education for its people, to a publicness of education owned by the people themselves.